ANALYSIS OF THE EFFECT OF HEALTHCARE SERVICE QUALITY ON THE MANAGEMENT OF DIABETES MELLITUS AMONG OUTPATIENTS AT MANISA COMMUNITY HEALTH CENTER, SIDENRENG RAPPANG REGENCY - Nurafifah; Khaeriyah Adri; Zulkarnain Sulaiman; Sunandar Said (CV. Fahr Publishing, 2026)
Diabetes mellitus is a chronic disease whose prevalence continues to increase, making it one of the major challenges in primary health care. At the Manisa Public Health Center, Sidenreng Rappang Regency, the number of diabetes mellitus cases increased from 310 in 2023 to 943 in 2025. This increase has intensified the workload of the public health center, highlighting the need to improve the quality of health services to ensure sustainable diabetes management. This study aimed to analyze the effect of health service quality, including service facilities and infrastructure, service mechanisms, and recording and reporting systems, on diabetes mellitus management, which was assessed through regular health check-ups, treatment adherence, and blood glucose monitoring among outpatients at the Manisa Public Health Center. This quantitative analytical study employed a cross-sectional design because it enabled the simultaneous measurement of the independent and dependent variables to examine their relationship. A total of 90 respondents were selected using simple random sampling. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that health service quality had a positive and significant effect on diabetes mellitus management (p = 0.005). Therefore, improving the quality of health services is essential to support optimal and sustainable diabetes mellitus management in primary health care.